Beyond the numbers : Unveiling trends in homeownership research - Mulyadi, Mulyadi; Nur Zaimah, Ubaidillah (MALQUE Publishing, 2023)
Homeownership has served as a pivotal tool in poverty alleviation research for an extended period. Its scope of observation has broadened, encompassing various dimensions such as social welfare, subjective well-being, and persisting inequality concerns, which continue to be of significant interest today. In this study, we conducted a bibliometric analysis focusing on the impact of homeownership as a means of household wealth accumulation, examining articles spanning from 2000 to 2021. While bibliometric reviews have been prevalent for over four decades, their application in the context of homeownership studies has been notably absent. Leveraging VOSviewer V.1.6.16, we analyzed 116 articles sourced from the Scopus database. Through cooccurrence analysis, we identified emerging areas of interest that can be concurrently explored alongside homeownership, including intergenerational transfers, borrowing constraints, capital gains, cultural economics, and wealth inequality. Additionally, our findings indicate a relative dearth of homeownership studies focused on developing countries, prompting inquiry into the suitability of employing homeownership as a poverty reduction strategy in such contexts.